2003
DOI: 10.1177/0306624x03251088
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Communities and Prison Management: An Examination of the Effects of Operating an In-Prison Therapeutic Community on Levels of Institutional Disorder

Abstract: There is a growing emphasis in corrections on the treatment of inmates with drug problems. The typical method of evaluating drug treatment programs is to examine how the treatment affects the inmate in terms of relapse and recidivism. This study examines the institutional consequences of operating a therapeutic community located in a medium/high-security male institution. The effect on management is examined from a perspective of institutional disorder. Disorders, from less severe inmate rule violations to mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 9 publications
3
20
0
Order By: Relevance
“…In particular, these findings highlight the importance of subverting the "jungle" culture that exists in prison, and to soften the pervasiveness of the gendered norms that appear to exist in prison around expressing emotions. As is alluded to in these findings, and supported by previous research (79), such a culture is attainable, since prisoners often recognize the culture in therapeutic communities as being markedly different, and more beneficial, than the "jungle" environment of prison main wings. Furthermore, several community campaigns center on the notion of encouraging men to discuss their feelings (e.g., Campaign Against Living Miserably, https://www.thecalmzone.net/), and the findings here suggest that a similar educational campaign may be of benefit in a male prison environment.…”
Section: Clinical and Research Recommendationssupporting
confidence: 76%
“…In particular, these findings highlight the importance of subverting the "jungle" culture that exists in prison, and to soften the pervasiveness of the gendered norms that appear to exist in prison around expressing emotions. As is alluded to in these findings, and supported by previous research (79), such a culture is attainable, since prisoners often recognize the culture in therapeutic communities as being markedly different, and more beneficial, than the "jungle" environment of prison main wings. Furthermore, several community campaigns center on the notion of encouraging men to discuss their feelings (e.g., Campaign Against Living Miserably, https://www.thecalmzone.net/), and the findings here suggest that a similar educational campaign may be of benefit in a male prison environment.…”
Section: Clinical and Research Recommendationssupporting
confidence: 76%
“…An increase in sense of belongingness is associated with reductions in suicidality and aggression, and an increase in feelings of well-being. These are areas in which TCs appear to have an effect (Barr et al, 2010; Dietz, Connell, & Scarpitti, 2003; De Leon, Sacks, Staines, & McKendrick, 2000; Shuker, Sullivan, & Rivlin, 2010). Reductions in aggressive and disruptive incidents in prison TCs (Dietz, Connell, & Scarpitti, 2003; Newton 2010) tally specifically with research linking lack of belongingness to aggression and paucity of prosocial skills.…”
Section: Belongingnessmentioning
confidence: 99%
“…Research on TCs in correctional facilities has found that the TC environment was better than that of the general population, meaning there were demonstrably lower levels of disorder and that inmate perceptions of the environment were more positive (Dietz, O'Connell, & Scarpitti, 2003). Peat and Winfree (1992) warned that the biggest threat to the TC model is the prison subculture and prisonization, aspects of prison life that are often noted to work to the disadvantage of mentally ill inmates.…”
Section: Environments As Therapymentioning
confidence: 99%